Nitrogen in Agriculture Physiological, Agricultural and Ecological Aspects - Ohyama, Takuji; Inubushi, Kazuyuki (IntechOpen, 2021)
Nitrogen is the most important nutrient in agricultural practice because the availability of nitrogen from the soil is generally not enough to support crop yields. To maintain soil fertility, the application of organic matters and crop rotation have been practiced. Farmers can use convenient chemical nitrogen fertilizers to obtain high crop yields. However, the inappropriate use of nitrogen fertilizers causes environmental problems such as nitrate leaching, contamination in groundwater, and the emission of N2O gas. This book is divided into the following four sections: "Ecology and Environmental Aspects of Nitrogen in Agriculture", "Nitrogen Fertilizers and Nitrogen Management in Agriculture", "N Utilization and Metabolism in Crops", "Plant-Microbe Interactions".